2023
DOI: 10.2147/dmso.s396621
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Continuum of Dysglycaemia and Vascular Complications in Prediabetes and Type 2 Diabetes: Need for Early and Intensive Treatment

Abstract: The onset of type 2 diabetes increases the risk of vascular complications and death. We know now that that this risk begins long before the diabetes diagnosis. Prediabetes and type 2 diabetes are not separate entities in practice and exist within a continuum of dysglycaemia and vascular risk that increases in severity over time. This excess risk requires early intervention with lifestyle therapy supported with pharmacologic antidiabetic therapy, intensified promptly where necessary throughout the duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…A clinical control study observed that about 19.4% of patients with impaired glucose tolerance reported peripheral neuropathic symptoms 36. While an earlier small-scale survey did not find a significant difference in DPN incidence between glucose-impaired individuals and the general population,37 recent researchers generally agree that DPN occurrence is a continuous process along with impaired glucose and diabetes diagnosis 38. Therefore, early intensified glucose intervention is crucial for preventing diabetic microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical control study observed that about 19.4% of patients with impaired glucose tolerance reported peripheral neuropathic symptoms 36. While an earlier small-scale survey did not find a significant difference in DPN incidence between glucose-impaired individuals and the general population,37 recent researchers generally agree that DPN occurrence is a continuous process along with impaired glucose and diabetes diagnosis 38. Therefore, early intensified glucose intervention is crucial for preventing diabetic microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…36 While an earlier small-scale survey did not find a significant difference in DPN incidence between glucose-impaired individuals and the general population, 37 recent researchers generally agree that DPN occurrence is a continuous process along with impaired glucose and diabetes diagnosis. 38 Therefore, early intensified glucose intervention is crucial for preventing diabetic microvascular complications. This study supports this view, suggesting that avoiding diabetic complications may require stricter blood glucose control standards than current diabetes diagnosis.…”
Section: Glycemic Traitsmentioning
confidence: 99%
“…Previous studies suggest that the prevalence of pre-diabetes in Nigeria ranged between 2.0% and 37.2%, while that of diabetes varied from 5% to 10%. 8 For a conservative sample size, we assumed the upper limits of the prevalence. Therefore, we assumed that the prevalence of the glycaemic disorder is 37.2%, at a 95% confidence level, 2.5% error margin, and a design effect of 1.5.…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%
“…Pre-diabetes (IGT and IFG) indicate an already heightened risk of cardiovascular disease ( 3 , 6 , 7 ), and their recognition compels urgent interventions that can lead to the prevention of type 2 diabetes and its complications ( 8 ). Fasting blood glucose and 2-h oral glucose tolerance test (OGTT) are the traditional methods of screening and diagnosis of diabetes.…”
Section: Introductionmentioning
confidence: 99%